2021
DOI: 10.1530/ec-20-0527
|View full text |Cite
|
Sign up to set email alerts
|

Higher blood pressure in normal weight women with PCOS compared to controls

Abstract: Objective: Obesity is considered to be the strongest predictive factor for cardio-metabolic risk in women with polycystic ovary syndrome (PCOS). The aim of the study was to compare blood pressure (BP) in normal weight women with PCOS and controls matched for age and BMI? Methods: From a Nordic cross-sectional base of 2,615 individuals of Nordic ethnicity, we studied a sub cohort of 793 normal weight women with BMI<25 kg/m2 (512 women with PCOS according to Rotterdam criteria and 281 age and BMI-matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The findings were in accordance with that there is a close relationship between BMI and BP. The mechanism underlying the increased prevalence of hypertension in PCOS has been linked to several factors such as hyperinsulinemia, hyperandrogenemia, and obesity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings were in accordance with that there is a close relationship between BMI and BP. The mechanism underlying the increased prevalence of hypertension in PCOS has been linked to several factors such as hyperinsulinemia, hyperandrogenemia, and obesity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Supporting these findings, a very recent study including a subcohort of 512 normal-weight women with PCOS (BMI < 25 kg/m 2 ) and 281 age-and BMI-matched controls from a Nordic cross-sectional base, reported that HTN was more common in PCOS subjects; however, after the age of 35 years, the prevalence of HTN was comparable in women with PCOS and controls. 49 Overall, available data suggest that increased risk of HTN in women with PCOS ameliorates with ageing and is similar to that of controls after menopause.…”
Section: Hypertensionmentioning
confidence: 94%
“…Moreover, blood pressure could be only mildly elevated as demonstrated in 24-hour ambulatory blood pressure measurements in women with PCOS ( 75 ). Obesity is associated with hypertension, but women with PCOS, even with normal weight, can have elevated blood pressure ( 76 ). The specific mechanism(s) that lead to elevated blood pressure or hypertension in PCOS remain a matter of debate.…”
Section: Hypertension and Sglt2 Inhibition In Pcosmentioning
confidence: 99%